ChemInform Abstract: Structural, Electrical, and Optical Properties of the Tetragonal, Fluorite‐Related Zn0.456In1.084Ge0.460O3. Issue 41 (October 2015) - Rickert, Karl; Sedefoglu, Nazmi; Malo, Sylvie; Caignaert, Vincent; Kavak, Hamide; Poeppelmeier, Kenneth R.
Abstract Zn0.456In1.084Ge0.460O3 is prepared by solid state reaction of ZnO, In2O3, and GeO2 (pellets in sacrificial powder in covered corundum crucible, 1250 °C, 16 h).